ANALYSIS OF COMMUNITY SATISFACTION INDEX (CSI) IN THE SOCIAL PROJECT: IMPLEMENTATION OF GOOD AGRICULTURAL PRACTICE (GAP) TO ENHANCE HIGH-LYCOPENE TOMATO CULTIVATION - Pathmi Noerhatini; Maryam Al Lubbu; Dicky Rezadi Munaf; Amanna Dzikrillah L. L. Hakim; Gilang Aditya Pratama; Christina Wijaya (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2025)
This study aims to evaluate the Community Satisfaction Index (CSI) associated with the implementation of Good Agricultural Practice (GAP) in enhancing high-lycopene tomato cultivation. Employing a quantitative survey design, the research assessed participant satisfaction across nine core components, including program requirements, procedures, service delivery, costs, staff competence, and infrastructure support. The results indicate a generally high level of satisfaction, with the overall CSI reaching 92.06, which classifies the program performance as “very good.” Among the assessed components, the Competence of Program Staff received the highest rating, reflecting the vital role of knowledgeable facilitators in ensuring program success. While most components were positively evaluated, facilities and infrastructure emerged as areas requiring further development to enhance long-term sustainability. The use of simple yet impactful technologies, coupled with clear communication and open knowledge-sharing sessions, contributed to the program’s positive reception. These findings suggest that the program was well-accepted by the community and is considered feasible for continuation and potential expansion in similar agricultural contexts.